Game format alters the physiological and activity demands encountered during small-sided football games in recreational players - Emilija Stojanović; Nenad Stojiljković; Ratko Stanković; Aaron T. Scanlan; Vincent J. Dalbo; Zoran Milanović (Elsevier, 2021)
Background: Conditioning in the form of football small-sided games (SSG) is being increasingly utilized as a health-promoting and performance-enhancing activity. Objective: The aim of this study was to quantify and compare the physiological responses and activity demands encountered during 3-a-side, 4-a-side, and 5-a-side football SSG in recreational players. Method: Heart rate, blood lactate (BLa), rating of perceived exertion (RPE) and activity demands were measured across 2 × 20-min football sessions played on a 40 × 20-m pitch in 12 recreationally active college students. Data were collected over a period of two weeks using a repeated-measures crossover design. Results: Mean heart rate was higher (moderate) during 5-a-side than 4-a-side (p = 0.02) and 3-a-side SSG (p < 0.001). BLa tended to be higher (small) in 3-a-side compared to 4-a-side (p = 0.12) and 5-a-side SSG (p = 0.46). The total distance covered was lower (large) during 5-a-side than 4-a-side SSG (p = 0.02), while the total number of accelerations (p = 0.01) and decelerations (p = 0.02) were higher (large) during 5-a-side than 4-a-side SSG. Conclusion: These data suggest: 1) 5-a-side SSG require a greater intermittent workload and exacerbated HR responses; 2) 4-a-side SSG require more sustained activity (distance); and 3) 3-a-side SSG result in higher BLa compared to other SSG formats. The observed intermittent workload and exacerbated HR response in 5-a-side SSG were likely due to greater turnover rates with more frequent interceptions. Sustained activity in 4-a-side SSG might be underpinned by format-specific structures permitting optimal team work, while isolated guarding of players in 3-a-side SSG may have exacerbated BLa responses.